IT controls in the public cloud: Success factors for allocation of roles and responsibilities. Issue 3 (7th September 2016) - Khan, Shafaq; Nicho, Mathew; Takruri, Haifa
ABSTRACT: The rapid adoption of cloud computing by organizations has resulted in the transformation of the roles and responsibilities of staff in managing the information technology (IT) resources (via IT governance controls) that have migrated to the cloud. Hence, the objective of this research is to provide a set of success factors that can assist IT managers to allocate the roles and responsibilities of IT controls appropriately to staff to manage the migrated IT resources. Accordingly, we generated a set of success factors from behavioral and information systems (IS) literature. These success factors were verified using in-depth interviews of executives from the United Arab Emirates (UAE). The empirical intervention suggests that the role allocation is driven predominantly by people's skills, competencies, organizational strategy, structures, and policies. In addition, the research made clear that the most significant competency and skill for a person allocated to IT controls is to be able to evaluate and manage a cloud service provider, especially in terms of risks, compliance, and security issues related to public cloud technology. The findings of this study not only offer new insights for scholars and practitioners involved in assigning responsibilities but also provide extensions for IT governance framework authorities to align their guidelines to the emerging cloud technology.